FACTORS INFLUENCING MOTHERS’ SUPPLEMENTARY FOOD PROVISIONS TO INFANTS AGED 0-6 MONTHS IN THE ONOLALU PUBLIC HEALTH CENTER WORKING AREA, ONOLALU DISTRICT, NIAS REGENCY, 2023 - Telambanua, Miamati; Srilina Br Pinem; Lusiatun; Himawari Kirina Petranela Sriyani; Ridesman; Apriani Triana Sari Ginting; Frafma Mursila (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
While exclusive breastfeeding is the gold standard for infants under six months, the premature introduction of complementary foods (MP-ASI) remains a widespread practice. This research investigated the determinants of early supplementary feeding among mothers within the Onolalu Health Center’s jurisdiction in Nias Regency. Employing a descriptive quantitative method with a cross-sectional framework, the study surveyed 34 participants via total sampling. Statistical analysis using the chi-square test identified maternal knowledge and employment status as critical factors (p = 0.000 ). In contrast, the origin of information did not demonstrate a meaningful correlation (p = 0.173). These results suggest that healthcare practitioners must prioritize ongoing counseling to foster better understanding of breastfeeding protocols.